The Physical Fitness Level of Children with Special Needs During the Covid-19 Pandemic In Extraordinary Schools - Slamet Raharjo; Olivia Andiana; Pandu Alief Wicaksono; Muhammad Taufik Triantoro (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze the level of physical fitness of children with special needs in pandemic Coronavirus Disease 2019 (COVID-19) at Sekolah Luar Biasa (SLB) Widya Santika Karangploso Malang.  This study is non-hypothetical descriptive, so there was no hypothesis formulation.  The results of this study are described the physical fitness levels of children with special needs in pandemic at SLB Widya Santika Karangploso Malang.  The study population is all students in SLB Widya Santika Karangploso Malang, there is 60 students.  Data analysis used quantitative descriptive data analysis techniques, that is scores for each item are summed and the results are compared with the expected score or ideal score.  The results obtained were 16.7% of children with special needs classified a level of physical fitness in the "good"; 21.6% “medium”; 48.3% “less”; 28.3% “very little”. In general, concluded that the mean physical fitness levels of children with special needs in pandemic COVID-19 at SLB Widya Santika Karangploso Malang were classified as "less" level. The results of this study can be used as evaluation material for teachers in improving students' physical fitness, especially for students with disabilities in pandemic COVID-19.